2018
DOI: 10.4314/mmj.v30i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive Compulsive Inventory – Child Version (OCI-CV): Confirmatory factor analysis, reliability, validity and correlates among Nigerian adolescents

Abstract: BackgroundObsessive compulsive symptoms (OCS) have not been studied among Nigerian adolescents, despite studies in developed countries reporting that almost 90% of affected adolescents do not receive any treatment. The availability of a psychometrically valid and reliable instrument will serve as an initial step towards the diagnosis and subsequent treatment of Nigerian adolescent obsessive compulsive disorder (OCD).AimsThe aim of this study was to examine the psychometric characteristics as well as correlates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…These findings are consistent with several studies conducted in adolescent populations [41][42][43][44]. However, other studies did not find the gender differences in adolescents [15,36,45,46]. Therefore, it could be argued that this is a topic on which there is some controversy, and more research is still needed to reach a consensus.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with several studies conducted in adolescent populations [41][42][43][44]. However, other studies did not find the gender differences in adolescents [15,36,45,46]. Therefore, it could be argued that this is a topic on which there is some controversy, and more research is still needed to reach a consensus.…”
Section: Discussionsupporting
confidence: 90%
“…The OCI-CV has been validated in clinical and non-clinical populations in Africa, Asia, Europe, North and South America. It has demonstrated good internal consistency (Cronbach's α = .83 -.91) and acceptable test-retest reliability (r = 0.77 -0.82; ICC = .85 -.92) in clinical and nonclinical populations (67,(126)(127)(128)(129)(130), with some evidence for its sensitivity to change (67). A parent-version of the OCI-CV is not currently available, and the Standard Set recommends collecting only youth report until a matching parentreport becomes available.…”
Section: Fundingmentioning
confidence: 99%
“…Previous validation studies of the OCI-CV, carried out in both clinical OCD samples [5,11,12] and community samples [12][13][14][15][16][17][18], have found it to be a reliable and valid measure of OCD, and to possesses a 6-factor structure. For example, in the original validation study employing a clinical sample (N = 100; aged 7 to 17 years) of youth with OCD, the authors observed a 6-factor structure, good test-retest reliability, and adequate sensitivity to change in the overall severity of OCD symptoms during treatment [5].…”
Section: Introductionmentioning
confidence: 99%